2022
DOI: 10.1055/a-1783-9015
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Barrett’s esophagus using wide-area transepithelial sampling: systematic review and meta-analysis

Abstract: Background and study aims Wide-area transepithelial sampling (WATS) is an emerging technique that may increase dysplasia detection in Barrett’s esophagus (BE). We conducted a systematic review and meta-analysis of patients who underwent surveillance for BE assessing the additional yield of WATS to forceps biopsy (FB). Methods We searched Pubmed, Embase, Web of science, and the Cochrane library, ending in January 2021. The primary outcomes of interest were the relative and absolute increase in dysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Wide-area transepithelial sampling (WATS) utilizing brushings is a useful adjunct to biopsies during endoscopy and allows sampling of a larger surface area-this device received societal endorsement ( 26 ). A meta-analysis demonstrated that the incremental yield of WATS for dysplasia was largely dependent on the dysplasia rate within the study populations and ranged from 2% to 13% ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wide-area transepithelial sampling (WATS) utilizing brushings is a useful adjunct to biopsies during endoscopy and allows sampling of a larger surface area-this device received societal endorsement ( 26 ). A meta-analysis demonstrated that the incremental yield of WATS for dysplasia was largely dependent on the dysplasia rate within the study populations and ranged from 2% to 13% ( 47 ).…”
Section: Discussionmentioning
confidence: 99%